CropCircles: Topology Sensitive Visualization of OWL Class Hierarchies - Taowei David Wang; Bijan Parsia (ISWC'06: Proceedings of the International Semantic Web Conference, 2006)
OWL ontologies present many interesting visualization challenges. Here we present CropCircles, a technique designed to view the class hierarchies in ontologies as trees. We place special emphasis on topology understanding when designing the tool. We drew inspiration from treemaps, but made substantial changes in the representation and layout. Most notably, the spacefillingness of treemap is relaxed in exchange for visual clarity. We outline the problem scape of visualizing ontology hierarchies, note the requirements that go into the design of the tool, and discuss the interface and implementation. Finally, through a controlled experiment involving tasks common to understanding ontologies, we show the benefits of our design.